Improving Transgenesis Efficiency and CRISPR-Associated Tools Through Codon Optimization and Native Intron Addition in Pristionchus Nematodes. Issue 4 (1st December 2020) - Han, Ziduan; Lo, Wen-Sui; Lightfoot, James W; Witte, Hanh; Sun, Shuai; Sommer, Ralf J
Abstract: A lack of appropriate molecular tools is one obstacle that prevents in-depth mechanistic studies in many organisms. Transgenesis, clustered regularly interspaced short palindromic repeats (CRISPR)-associated engineering, and related tools are fundamental in the modern life sciences, but their applications are still limited to a few model organisms. In the phylum Nematoda, transgenesis can only be performed in a handful of species other than Caenorhabditis elegans, and additionally, other species suffer from significantly lower transgenesis efficiencies. We hypothesized that this may in part be due to incompatibilities of transgenes in the recipient organisms. Therefore, we investigated the genomic features of 10 nematode species from three of the major clades representing all different lifestyles. We found that these species show drastically different codon usage bias and intron composition. With these findings, we used the species Pristionchus pacificus as a proof of concept for codon optimization and native intron addition. Indeed, we were able to significantly improve transgenesis efficiency, a principle that may be usable in other nematode species. In addition, with the improved transgenes, we developed a fluorescent co-injection marker in P. pacificus for the detection of CRISPR-edited individuals, which helps considerably to reduce associated time and costs.